2018
DOI: 10.3390/ijms19051323
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish, a Novel Model System to Study Uremic Toxins: The Case for the Sulfur Amino Acid Lanthionine

Abstract: The non-proteinogenic amino acid lanthionine is a byproduct of hydrogen sulfide biosynthesis: the third endogenous vasodilator gas, after nitric oxide and carbon monoxide. While hydrogen sulfide is decreased in uremic patients on hemodialysis, lanthionine is increased and has been proposed as a new uremic toxin, since it is able to impair hydrogen sulfide production in hepatoma cells. To characterize lanthionine as a uremic toxin, we explored its effects during the early development of the zebrafish (Danio rer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The effect of lanthionine may contribute to an overall impairment of transsulfuration, thus help explaining the presence of a very high prevalence of hyperhomocysteinemia in uremia, which so far has otherwise gone unexplained. As far as the second aspect is concerned, previous evidence showed that such damaging effects do actually take place in zebrafish, although the molecular mechanism was still elusive [7]. Data presented here showed that the induction of a more reducing cellular microenvironment, due to the presence of GSH, tends to hamper lanthionine effects on the transsulfuration enzyme CBS.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The effect of lanthionine may contribute to an overall impairment of transsulfuration, thus help explaining the presence of a very high prevalence of hyperhomocysteinemia in uremia, which so far has otherwise gone unexplained. As far as the second aspect is concerned, previous evidence showed that such damaging effects do actually take place in zebrafish, although the molecular mechanism was still elusive [7]. Data presented here showed that the induction of a more reducing cellular microenvironment, due to the presence of GSH, tends to hamper lanthionine effects on the transsulfuration enzyme CBS.…”
Section: Discussionmentioning
confidence: 72%
“…Previous results have shown that lanthionine induces significant changes in the miRNA pattern in zebrafish larvae; these changes were partly comparable to some miRNA modifications detected in uremia [7]. In this work, we undertook a literature search and choose miR-200c and miR-423 since they are altered in kidney disease [14,15,16,17,18,19,20].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…H 2 S is also significantly lower in plasma from CKD and hemodialysis patients compared to controls, while the metabolic related compounds cystathione, homolanthionine and lanthionine are significantly increased [58]. In this respect, lanthionine, a byproduct of the transsulfuration pathway found to be quite high in the plasma of CKD patients, is able to exert several toxic effects [59][60][61][62]. Lanthionine is also an end product of bacterial metabolism.…”
Section: Sulfur Compoundsmentioning
confidence: 99%
“…H 2 S is biosynthesized through enzymatic reactions in human tissues, although 50% of this gas is generated by the microbiota, in the inner and outer mucus layers of the intestine [1]. In the last two decades, the metabolism and physiological roles of H 2 S and its derivatives, such as the amount released from Fe-S proteins and sulfane sulfur species, have been also related to various pathological situations [2,3]. Controversies have been raised on the physiological H 2 S active concentrations, which have been detected in the 10 −5 −10 −4 molar range [4,5].…”
Section: Introductionmentioning
confidence: 99%